Clinical and endoscopic remission in patients with inflamatory bowel disease using aminosalicilates, systemic corticoesteroids and immunomodulators (Boletin Médico de Postgrado, 2023)
A cross-sectional transversal research was conducted with the aim of determining clinical and endoscopic remission of inflammatory bowel disease (IBD) with the use of aminosalicylates, systemic corticosteroids and immunomodulators in patients attended at the Servicio de Gastroenterologia of the Hospital Central Universitario Dr. Antonio María Pineda, Barquisimeto, Lara state, during the period 2012-2020, using the Montreal, Mayo, CDEIS, Harvey-Bradshaw and Harvey-Bradshaw indices. The population consisted of 87 records from the clinical histories of patients who met the established criteria. The prevalence age was between 41 and 62 years; 65.5% were females. 44.9% of patients with ulcerative colitis (UC) showed left colitis and 34.6% pancolitis. In Crohn’s disease (CD), 88.9% of patients showed an inflammatory pattern. Clinical activity of UC at diagnosis was mild (47.7%) and moderate (44.9%). After induction, 87% of patients who did not achieve clinical remission were found to have mild activity. In CD at diagnosis, mild clinical activity prevailed (77.8%). Endoscopic activity at UC diagnosis was moderate (56.4%) and severe (32.1%) and at control colonoscopy during maintenance therapy, the percentage of patients in mild/ moderate activity was 40% in both groups. In UC, prednisone (47.4%) or mesalazine (24.3%) was used for induction and for maintenance, azathioprine + mesalazine or sulfasalazine (35.9% and 25.6%), respectively. In CD, prednisone (88.9%) was used for induction and for maintenance, aminosalicylates (77.8%) and aminosalicylates + azathioprine (22.2). In UC, 70.5% presented clinical remission and 29.5% endoscopic remission. In CD, 88.9% showed clinical remission and 33.3% endoscopic remission.
Keywords: intestinal diseases; colitis, ulcerative; Crohn disease; endoscopy, digestive system; anti-inflammatory agents